Impact of Quality Management System Practices on the Business Performance of a Government Corporation in Clark Freeport Zone, Philippines - Quiambao, Jherson L.; Alvaro, Karlo Nicolas G. (Future Science / FSH-PH Publications, 2023)
Quality Management System [QMS] is an emerging management philosophy that takes its course amid today’s competitive and dynamic global markets where quality becomes a critical factor of business excellence. Discovering its value as a success factor, many studies were conducted to determine the level of influence of QMS practices on the business performance. Invested from the non-consensus findings from these studies and the scarcity of published papers about QMS in Philippine government corporations, the researchers conducted quantitative research in a government corporation in Clark Freeport Zone, Philippines, designed with descriptive, cross-sectional, causal-comparative framework to determine the impact of the QMS practices on its business performance. A 40-item close-ended survey instrument, tested for validity and reliability, was developed to measure the QMS practices in the context of the ISO 9001:2015 QMS, and the Business Performance in the perspectives of the Balanced Scorecard. This was accommodated by 125 respondents, representing 88% of its target population. Results revealed that the QMS practices dimensions top management leadership, customer orientation, process control and improvement, and employee engagement each had significant positive impact on each business performance perspectives financial, customer, internal business processes, and innovation and learning of the subject government corporation. Determining the influence of quality practices on business performance is significantly relevant in government corporations since these entities act as both a public sector and a business entity. It creates an opportunity for the Philippine leaders to justify the national thrust of delivering quality-oriented government service to the Filipino people.